Analisis Struktur Baja Tahan Gempa dengan Sistem SRPMK (Struktur Rangka Pemikul Momen Khusus) Berdasarkan SNI 1729:2015 dan SNI 1726:2012 - Zachari, M.Y.; Turuallo, G. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2020)
The selection of material is one of the important aspects used to design a building as it is known that every type of material has a different characteristic. The steel material used as the main component of building structure because of its ductility is more than another material which is the main criterion to design an earthquake resistance building. In this paper, an earthquake steel resistant structure building will be design. This building structure will consist of a five-story office with a regular structure configuration. A special moment frame (SMF) used as the resisting structure system of the earthquake loads as the amount of its load is analyzed using the spectrum response method. The steel material used is type of A36 (fy = 250 MPa; fu = 400 MPa), concrete used f’c = 30 MPa. The design process then produces an earthquake steel resistant structure building, which satisfies the requirement of story drift with a maximum number of story drift occurred in the 2nd story which is 93.5 mm less than allowed story drift that is 95 mm. A structure element dimension used is a beam with a profile of W16x7x40 for every level in the X-axis direction, and the beam with a profile is W14x6.75x38 for every level in Y-axis direction, 12 cm thick plates and column with a profile W14x16x211 is regularly used to every level.